Adding scent: exploring improvements in pan trapping to monitor pollinators - Dunlap, Madison M.; Casey, Christina R.; VanOverbeke, Dustin R. (Frontiers in Bee Science, 2023)
Our project assessed whether adding floral scents to pan traps would increase the abundance and/or diversity of Hymenoptera sampled or decrease bycatch. We sampled insects using white pan traps containing 0.5 mL of floral scent (linalool, phenylacetaldehyde, limonene, geraniol, benzaldehyde, no scent control) per liter of trapping solution in an interior southern California natural space. Scented traps shared between 53.0-79.7% similarity in Hymenoptera assemblage and 59.5-72.2% similarity when using presence/absence data as compared with the control. Phenylacetaldehyde and geraniol increased the capture rate of new Hymenoptera while phenylacetaldehyde also increased overall Hymenoptera and bycatch capture rate. Additionally, we noted that phenylacetaldehyde traps increased small parasitoid wasp capture tenfold, potentially indicating an alternative use for the addition of phenylacetaldehyde to pan traps. We found no evidence that the addition of scent decreased the abundance or diversity of Hymenoptera caught. Those seeking to exhaustively record the species richness in an area may benefit the most from this method with potential to increase capture of large bodied, rare, or specialist pollinating Hymenoptera with scent preference, though further research is needed. Based on the data presented here, scent should be explored further for its effect on pan trap catch.